Efecto del plasma sanguíneo porcino suplementado a dieta post·destete sobre la performance de gorrinos comerciales a los 70 días de edad - Ñique Chacón, Andrés Alberto (2012)
The research objective was to evaluate the effect of porcine blood plasma supplemented in post-weaning diet on the performance of commercial piglets at 70 days of age, in CICOPSAC pig farm, located in the province ofHuaral. It were used 60 piglets weaned at 21 days old, divided into 2 treatments of 30, under a completely randomized design. The diet for the control treatment was commonly used in farm and plasma treatment had levels of inclusion of 5% for first 34 days (divided into stages of 10, 11 and 13 days) and 2% for the nex:t 15 days and were supplied ad libitum. The results of weight gain, feed intake and feed conversion were evaluated statistically with t Student's test, and the rates of morbidity and mortality with the Chi Square test. The total weight gain of piglets was statistically higher (p<0.01) in blood plasma treatment than in the control (22.43 kg vs. 21.52 kg), the same statistical difference was showing in total feed consumption (775.7 kg vs .. 705.6 kg). Feed conversion was numerically better for the control treatment, but without statistically significant differences (1,131 vs. 1.153). Likewise, no statistical differences were found for the parameters of percentage of morbidity and mortality rate. The benefit 1 cost of the diets was 1.37 and 1.34 for treatment with blood plasma and witness respectively. In conclusion, treatment with blood plasma was higher than the control treatment.